Application of agroforestry to African crop-livestock farming systems - Tothill, J.C. (1987)
Discusses the potential of leguminous trees to increase crop-livestock production in sub-Saharan Africa. Describes major management issues influencing tree introduction and contributions to the system. Gives a detailed account of the management techniques suitable for different agro-ecological zones.